2017
DOI: 10.5539/ibr.v10n10p39
|View full text |Cite
|
Sign up to set email alerts
|

Does the Monitoring Mechanisms Considered as Dilemma against the Practices of Earnings Management

Abstract: This paper mainly aims to explore the role of monitoring mechanisms in limiting the earnings management practices among service firms in Jordan. The data used in this study were from the financial annual reports of 59 ASE listed service firms in 2015. The results of multiple regression analysis demonstrate the fairly varied influence of board of directors' variables. This paper presented three hypotheses covering board independency, CEO duality and audit committee. According to the results, internal monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In addition to the above, several studies conducted in the Jordanian environment have indicated that most Jordanian companies have practiced earnings management in their statements. The consequences of practices of earnings management are beyond doubt detrimental, decreasing the value of a company, its transactions, its image and its reputation, (Sraheen & Saleh, 2017;Ajeleh & Hamdan, 2009). These detrimental consequences are in addition to the fear of the collapse of large Þ rms as has happened in developed countries, as mentioned previously (Rodriguez-Ariza, Rodriguez-Ariza, Martínez-Ferrero, Martínez-Ferrero, Bermejo-Sánchez & Bermejo-Sánchez, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above, several studies conducted in the Jordanian environment have indicated that most Jordanian companies have practiced earnings management in their statements. The consequences of practices of earnings management are beyond doubt detrimental, decreasing the value of a company, its transactions, its image and its reputation, (Sraheen & Saleh, 2017;Ajeleh & Hamdan, 2009). These detrimental consequences are in addition to the fear of the collapse of large Þ rms as has happened in developed countries, as mentioned previously (Rodriguez-Ariza, Rodriguez-Ariza, Martínez-Ferrero, Martínez-Ferrero, Bermejo-Sánchez & Bermejo-Sánchez, 2016).…”
Section: Introductionmentioning
confidence: 99%